Answer:
n = -5
Explanation:
6n + 12 − 8n = 22
[ Simplify both sides of the equation ]
6n + 12 − 8n =22
6n + 12 + −8n = 22
(6n + −8n) + (12) = 22 [Combine Like Terms]
−2n + 12 = 22
−2n + 12 =22
[ Subtract 12 from both sides ]
−2n + 12 − 12 = 22 − 12
−2n = 10
[ Divide both sides by -2 ]
-2n / -2 = 10 / -2
n = -5
Answer:
n = -5
Step-by-step explanation:
6n + 12 - 8n = 22
Combine like terms
-2n +12 = 22
Subtract 12 from each side
-2n +12-12 = 22-12
-2n =10
Divide each side by -2
-2n/-2 = 10/-2
n = -5